Exploring temporary urban interventions through user activities: a case study of Abdali Boulevard, Amman, Jordan - Sharif, Ahlam Ammar (Frontiers in Built Environment, 2023)
Urban studies have examined the potential of urban interventions to upgrade spaces. This is the focus of relational approaches that emphasize interactions between interventions and users. One approach, actor–network theory, views these interactions as temporary stabilized relational effects. Despite its usefulness in uncovering diverse interactions in urban spaces, the utilization of actor–network theory in unpacking these relations has been limited. This study utilized an actor–network theory-inspired ethnography in a temporary urban intervention in Abdali Boulevard, in Jordan, to bridge this gap. It relied on desk research, interviews, and site observations to explore the different intervention–user interactions. The findings revealed various interactions and relational patterns occurring between interventions and their users through their presence and absence in space and time, where users attended to, engaged with, overlooked, bypassed, disturbed the intervention, or floated between different modes of interaction. Unpacking these diverse interactions and relations provides a nuanced perspective on the effects of urban interventions on spaces.